Scanning electron microscopy of Spinochordodes tellinii (Camerano, 1888), (Gordiacea, Nematomorpha) - Villalobos, Leonor Cristina de (2002)
There are many species of Nematomorpha which are deficiently described and therefore pose doubts about their actual taxonomic position. This is the case with Spinochordodes tellinii (Camerano, 1888), which was transferred to four different genera and has been recently considered as species incertae sedis. A female of Spinochordodes tellinii is redescribed in this work under light microscopy and Scanning Electron Microscopy. Cuticle details, shapes and areolar distribution and the features as well as the location of spiniform structures are analysed. The systematic position is discussed.